PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNINGUNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS VISDN 013 LUBUK KEMBANG SARI KECAMATAN UKUI - Muhroni ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the lack of PKn student learning outcomes, it is due to lack of significance for learning the teacher, the teacher gives no concrete contohyang and juah of environmentally friendly, passive students in participating in learning. This study is a class action that aims to improve learning outcomes PKn, as well as improving the learning activities of teachers and students using a contextual approach to teaching and learning. Research was conducted during two cycles, where research on SDN 013 Lubuk Kembang Sari Kecamatan Ukui with research subjects are students of class VI. Data collection techniques used in this study was the observation techniques, test engineering and technical documentation. The analysis technique used is descriptive analysis. Based on the results of research and discussion, found that the learning outcomes of students has increased at each cycle, is strengthened by the results that have been raised previously, namely: (1) early mastery learning outcomes of Civic Education students gain is 45%; (2) in the first cycle completeness PKn learning outcomes of students increased by 70%; and (3) in the second cycle completeness PKn learning outcomes of students increased by 80%. This indicates that the completeness kasikal has been reached, in which the research is successful if the completeness achieved 80% of students obtaining a minimum value of 65. Based on the results and the discussion can be concluded that the application of contextual teaching and learning approach to improving student learning outcomes PKn Class VI SDN 013 Lubuk Kembang Sari Kecamatan Ukui.